Improving Psychological Outcomes for North Korean Refugees: A Research Agenda - Eric Taylor, Benjamin (International Journal of Psychosocial Rehabilitation, 2017)
North Korean refugees often experience persistent mental health concerns after departing from North Korea. These concerns may arise in relation to traumas experienced within North Korea, bereavement over separation from family members, and difficulties in adjusting to life outside North Korea. Post-traumatic stress disorder is common among North Korean refugees, yet there is a surprising lack of research investigating post-traumatic growth among this population. Post-traumatic growth involves global changes to one’s outlook on life, and is associated with reduced psychological symptom burden among trauma  survivors. Post-traumatic growth is an important component of recovery following trauma, and leads to better long term outcomes. There is a scarcity of research however investigating this phenomenon among North Korean refugees. In this short communication, a research agenda emphasising post-traumatic growth among North Korean refugees is emphasised. Areas for future research include the relationship between post-traumatic growth and autonomy, psychological grit and hardiness, and experiential avoidance. Rather than adopting a symptom-driven agenda, researchers should investigate adaptive functioning and the process of finding meaning among North Korean refugees.